Editorial: Paulo Freire: philosophy, education and language teaching as a human right - Gamboa, Silvio (Universidade Estadual de Campinas, 2022)
Editorial of n.2 (2021). Special issue, commemorating the centenary of the birth of educator and philosopher Paulo Freire.